The dark net eaudiobook Inside the digital underworld. - Bartlett, Jamie (Tantor Media, 2017)
In this important and revealing book, Jamie Bartlett takes us deep into the digital underworld and presents an extraordinary look at the internet we don't know. Beginning with the rise of the internet and the conflicts and battles that defined its early years, Bartlett reports on trolls, pornographers, drug dealers, hackers, political extremists, Bitcoin programmers, and vigilantes—and puts a human face on those who have many reasons to stay anonymous. Rich with historical research and revelatory reporting, The Dark Net is an unprecedented, eye-opening look at a world that doesn't want to be known.